Micro/Nanometer‐Structured Scaffolds for Regeneration of Both Cartilage and Subchondral Bone. (7th December 2018) - Deng, Cuijun; Lin, Rongcai; Zhang, Meng; Qin, Chen; Yao, Qingqiang; Wang, Liming; Chang, Jiang; Wu, Chengtie
Abstract: Treatment of osteochondral defects remains a great challenge in clinical practice because cartilage and subchondral bone possess significantly different physiological properties. In this study, the controlled surface micro/nanometer structure of bioactive scaffolds in a combination of biomaterial chemistry is harnessed to address this issue. Model bioactive biomaterials, bredigite (BRT) scaffolds, with controlled surface micro/nanostructure are successfully fabricated by combining 3D printing with a hydrothermal process. It is found that the growth of micro/nano–calcium phosphate crystals on the surface of BRT scaffolds notably enhances their compressive strength by healing the microcracks on the strut surface. The micro/nanostructured surface distinctly facilitates the spread and differentiation of chondrocytes by activating integrin αv b 1 and α5 b 1 heterodimers, regulates cell morphology, and promotes osteogenic differentiation of rabbit bone marrow stromal cells (rBMSCs) through the synergetic effect of integrin α5 b 1 and RhoA, in which the microrod surface demonstrates the highest stimulatory effect on the differentiation of chondrocytes and rBMSCs. The in vivo study shows that the micro/nanostructured surface of the 3D printed scaffolds obviously promotes the regeneration of both cartilage and subchondral bone tissues. This study suggests that the construction of controlled micro/nanostructured surface in porous 3D scaffolds offers a smart strategy to induce bilineage bioactivities for osteochondral regeneration. Abstract : Micro/nanostructured surfaces in bredigite scaffolds are successfully prepared via a hydrothermal process. In vitro, the micro/nanostructured surface significantly promotes differentiation of chondrocytes by activating integrins α5β1 and αvβ1, and stimulates osteogenic differentiation of rabbit bone marrow stromal cells through the synergetic effects of integrin α5β1 and RhoA. Furthermore, the micro/nanostructured surface possesses dual physiological functions for the regeneration of both cartilage and subchondral bone.